Whole-Exome Sequencing Identified Genes Responsible for Thoracic Aortic Aneurysms and Dissections in three Chinese Families - Guo, Renle; Du, Pengcheng; Pei, Yifei; Yang, Jin; Li, Shuangshuang; Chang, Sheng; Sun, Huiying; He, Xiaomin; Dong, Jian; Zhou, Jian; Jing, Zaiping (Frontiers in Genetics, 2022)
Thoracic aortic aneurysms and dissections is a critical condition that often goes undiagnosed with fatal consequences. Over the last few years, pathogenic variants in numerous genes have been identified that predispose to heritable presentations of TAAD. An evidence-based strategy for the selection of genes to test in familial TAAD helps inform family screening and intervention to prevent life-threatening events. Using whole-exome sequencing, four members of three unrelated families clinically diagnosed with TAAD were used to identify the genetic origin of the disorder. Variant evaluation was carried out to detect the pathogenic mutation. Our studies suggest that mutations of COL3A1, ACTA2 are responsible for non-syndromic TAAD. In addition, highlights COL4A5, FBLN5, FBN1, SLC2A10, FBN2 and NOTCH1 as candidate genes. Future studies of crosstalk among the pathways provided us a step toward understanding the pathogenic mechanism. This finding indicates the importance of obtaining detailed family history and screening of extended relatives of patients with TAAD to improve the outcome.